Anchoring when the anchors and the answers belong to different semantic categories - Martišius, Vaclovas; Černevičiūtė, Rūta (Psichologija, 2002)
By the investigation it was established that the anchors could affect the evaluations of the subjects, although the anchors and answers belonged to different semantic categories. The evaluations of the subjects having and not having professional knowledge differed significantly. It is likely that effective anchors changed the evaluation range of the subjects not having professional knowledge. The anchoring character of the subjects having professional knowledge dependent on the anchor size.